Management of primary lymphoma of the spleen in a patient with HIV-AIDS: Case report (International Journal of Medical and Surgical Sciences, 2020)
Primary splenic lymphomas involve the spleen and/or its lymph nodes. They represent
Keywords: Linfoma primario de bazo; esplenectomía; reporte de caso